A review of Euryobeidia Fletcher, 1979 (Lepidoptera, Geometridae, Ennominae), with description of three new species - Xiang, Lanbin; Xue, Dayong; Wang, Wenkai; Han, Hongxiang (Zootaxa, 2017)
The genus Euryobeidia Fletcher, 1979 is reviewed. Five species from China are recognized, of which, E. ellipsoidea sp. nov., E. incrassata sp. nov. and E. quadrata sp. nov. are described as new to science. Diagnoses for all the species are provided and illustrations of external features and genitalia are presented.